Analisis karakteristik periode ulang curah hujan dengan metode Iwai Kadoya di daerah lokal sumatera barat dan regional sumatera (Analysis of the characteristics of the return period of rainfall using the Iwai Kadoya method in the local area of West Sumatra and regional Sumatra) - Mia Nova Isnia Gara; Letmi Dwiridal; Sugeng Nugroho (PILLAR OF PHYSICS, 2019)
Sumatera is located in the western part of Indonesia, this result in the Sumatera region has high rainfall, due to the west monsun origaniting from the Indian Ocean a lot through the western part of Indonesia. Sumatera Island are divided into three major parts that have different regional topographies and type pf rainfall, so that characteristics of rainfall in Sumatera are different in each region. High rainfall results in natural disaster, to reduce the impact of disaster mitigation, the rainfall return periodis also used to predict the time needed to resume maximum rainfall. In this study, calculate the rainfall return period from 8 stations. From the calculation results it is known that the re-period of highest rainfall is at the Meteorogical Station of Minang Kabau Airport in the period 1999-2018 with a return period of 30 days- 300 years with the rainfall frequency pf 186-524 mm/day, with equatorial rain type.